Unusual Case of a Missing Vibrator Device in the Pelvis. (26th February 2020) - Marchand, Greg J.; Sainz, Katelyn M.; Azadi, Ali; King, Alexa; Anderson, Sienna; Ruther, Stacy; Brazil, Giovanna; Rials, Lisa; Ware, Kelly; Osborn, Asya; Hopewell, Sophia
Abstract : Emergency room admissions and surgery secondary to the malfunctioning of devices intended for sexual stimulation are extremely common. Emergency room staff in the United States are commonly skilled in the detection and removal of some of these frequent occurrences. Occasionally, surgical intervention can be warranted if the device enters a cavity that cannot safely be explored in the emergency room setting. We report a case of a vibrator which was lost during sexual activity and appeared on flat plate X-ray to be in the abdominal cavity. A careful history showed that the device was of an unusually narrow diameter, and surgical intervention showed the device ultimately ended up in the bladder without traumatic injury. Following laparoscopic confirmation of the device's location in the bladder, cystoscopic removal was performed and the patient recovered uneventfully.